Uptake of Joint Village Land Use Planning (JVLUP) by the Government of Tanzania - CGIAR Research Program on Livestock (2021)
In 2021 the Government of Tanzania released a revised edition of their manual for participatory village land use planning. The manual includes and promotes the joint village land use planning (JVLUP) approach, which ILRI has been supporting the government to develop and pilot. This will encourage the upscaling of JVLUP across the country improving the security of tenure of pastoralists and laying the foundation for improved rangeland management.